2013
DOI: 10.4103/0019-5413.106893
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty in extra articular deformities: A series of 36 knees

Abstract: Background:The presence of extra articular deformities either in the femur or the tibia with arthritis of the knee makes total knee arthroplasty (TKA) technically demanding. The purpose of this study is to report outcomes with Total Knee Arthroplasty in patients with arthritis of the knee associated with extra articular deformity by intraarticular resection and soft tissue balancing.Materials and Methods:Thirty six knees (32 patients) who had arthritis of the knee associated with extra articular deformity, und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The closer the deformity is to the joint, the greater impact the deformity has on the orientation of resection thus the farther deformity from the knee joint may be less in need of corrective osteotomy than those that are closer to the knee joint. 7,12 For TKR with extraarticular deformity, options include two-stage osteotomy, one-stage osteotomy, and one-stage intra-articular correction. 8 A two-stage osteotomy can be performed for extra-articular deformities that are thought to be too severe for intra-articular correction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The closer the deformity is to the joint, the greater impact the deformity has on the orientation of resection thus the farther deformity from the knee joint may be less in need of corrective osteotomy than those that are closer to the knee joint. 7,12 For TKR with extraarticular deformity, options include two-stage osteotomy, one-stage osteotomy, and one-stage intra-articular correction. 8 A two-stage osteotomy can be performed for extra-articular deformities that are thought to be too severe for intra-articular correction.…”
Section: Discussionmentioning
confidence: 99%
“…12 The vast majority of these deformities can be managed by intra-articular resection and careful ligamentous balancing. 7,9 Any planned resection that would compromise the integrity of the collateral ligament must be dealt with either by an osteotomy or by using metallic augmentation on the deficient side and limiting the resection on the prominent side to preserve the collateral ligament Resection much greater than 10 mm may jeopardize the origin of the collateral ligaments on the femoral side or affect the strength of the tibial bone stock on the tibial side.…”
Section: Discussionmentioning
confidence: 99%
“…PLLR is an adequate imaging exam for the planning of TKAs, as it allows the identification of extra-articular deformities and the estimation of the AFA, MFA, MTA, and AMFA. 8 …”
Section: Discussionmentioning
confidence: 99%
“…The main disadvantage of the medial approach is that it is more difficult to reach the posterolateral corner during the lateral soft tissue release [11,12] . Some authors reported that when a medial approach is performed in a valgus knee, the results have been inferior compared to varus deformity [13][14][15] .…”
Section: Approachesmentioning
confidence: 99%